Reproductive Freedom and the Paradigmatic Character of Plato's "Republic" - Thanassis Samaras (Center for Hellenic Studies, 2020)
In the Republic, the paradigmatic character of Plato’s best city appears incompatible with the use of deception in the procreative practices of the Auxiliaries and Guardians. I argue that this incongruity, as well as the exact provisions of Plato’s reproduction festival, are explained by three facts: his commitment to eugenics, his insistence on the abolition of the typical Greek household and his belief that there are serious limitations to the type of knowledge that Auxiliaries can achieve.